ANALISIS FOTOMETRI OBJEK API MENGGUNAKAN SOFTWARE IMAGE-J - Ikhwanul Qiram (Injection: Indonesian Journal of Vocational Mechanical Engineering, 2022)
Flame is a phenomenon of rapid oxidation of an element in a physical and chemical reaction process that produces heat, light, and other chemical products. Flame testing aims to quantify the presence of a particular element through the emission spectrum of each element. In addition, the physical characteristics of the fire object were also observed. Image-J software is one of the practical supporting applications that is often used for observing flame objects specifically in the fields of chemistry, physics, and energy. Experimental results have shown the level of accuracy of object dimensions and spectrometry with an accuracy rate of 97%. Differences in measurement ranges are often triggered by the image of the object and the foresight of the researcher.